Wild bees occupy temporally stable pollen nutritional niches - Anthony D. Vaudo; Jillian A. Luthy; Eva Lin; Sonja K. Glasser; Anne S. Leonard (Oecologia, 2026)
As bees’ primary source of protein and lipids, pollen is a nutritional resource key to the persistence of wild populations. Because bee taxa may differ in their pollen macronutrient requirements, and pollen is a limited resource that varies chemically across plants, nutritional niches may shape bees’ ecological interactions. To explore whether members of bee communities occupy pollen nutritional niches, we analysed the protein and lipid content of pollen collected by abundant bee subgenera ( Nomadopsis , Melanosmia , Eumelissodes , Pyrobombus ) and observed their pollen-collecting visitation to plant species at a single Sierra Nevada meadow across three years. We compared pollen nutrition and host plant visitation among subgenera, and at the species level within Pyrobombus. Subgenera exhibited clear and temporally consistent separation of pollen load macronutrition each year, achieved by either host-plant fidelity or flexibility when foraging. Pyrobombus species shared a nutritional niche, potentially creating competition for pollen macronutrients among species relieved by their taxonomic flexibility. These results offer some of the first evidence that nutritional niches among wild bee taxa are annually stable and demonstrate how different taxa may forage to achieve nutritional consistency. Relevant to bee conservation, our findings emphasize that a nutritionally diverse array of plants may be required to support wild bee communities.

Combined Ba-Cd isotope tracer in microbialites records biogeochemical metal cycling changes as a response to the Middle Miocene Badenian Salinity Crisis - Simon V. Hohl; Yi-Bo Lin; Philipp Gleissner; Eva E. Stüeken; Yuxiang Jiang; Sebastian Viehmann (Geochimica et Cosmochimica Acta, 2026)

Robust strategy for bioplastic production from cyanobacteria-enriched microbiomes: insights from gene expression and population dynamics - Beatriz Altamira-Algarra; Lin Sun; David San León Granado; Lucía Romero-Morillo; Livia Vurro; Juan Nogales; Eva Gonzalez-Flo; Joan Garcia (Chemical Engineering Journal, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Correction to: Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2025)

Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2024)

Importance of temporary and permanent snow for new second homes - Martin Thomas Falk; Eva Hagsten; Xiang Lin (International Journal of Biometeorology, 2024)
This study investigates empirically how natural snow depth and permanent snow affect the number of new second homes in Norway. One out of four Norwegian municipalities is partly covered by glaciers and permanent snow. In the winter seasons of 1983–2020, there is a decline in snow depth from 50 to 35 cm on average (based on 41 popular second-home areas in the mountains). Results of the fixed effects Poisson estimator with spatial elements show that there is a significant and positive relationship between natural snow depth in the municipality and the number of second homes started. There is also a significant and negative relationship between the number of new second homes in the municipality and a scarcity of snow in the surrounding municipalities. However, the magnitude of both effects is small. Estimates also show a strong positive relationship between the proportion of surface covered by permanent snow or glaciers in the municipality and new second homes. This implies that a decline in permanent snow and glaciers may make these areas less attractive for the location of second homes.

Spatial influence on the distribution of downhill skiers in Sweden - Martin Falk; Eva Hagsten; Xiang Lin (International Journal of Biometeorology, 2024)
This study investigates empirically how natural snow depth affects the number of downhill skiers. Data include the number of skier visits for the 32 largest ski resorts in Sweden from the 1998/1999 to the 2018/2019 seasons. Results of spatial dynamic estimations show that an increase in natural snow depth in the ski area has a significant negative impact on the number of skier visits in the short term, although the magnitude is small. This implies that a snow deficit leads to increased demand for downhill skiing both directly and indirectly (in the neighbouring areas). The variable snow depth in the neighbouring ski areas is not significantly different from zero, indicating that no spatial substitution takes place. There is, however, a strong positive relationship between skier visits to neighbouring areas, revealing that ski resorts are complements rather than substitutes. The long-term influence of snow depth is not significant, implying that the ski business is independent of variations in snow depth. Instead, the number of skier visits is mainly determined by past visits, revealing a high degree of persistence.

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Tire wear particles: An emerging threat to soil health - Jing Ding; Min Lv; Dong Zhu; Eva F. Leifheit; Qing-Lin Chen; Yun-Qing Wang; Ling-Xin Chen; Matthias C. Rillig; Yong-Guan Zhu (Critical Reviews in Environmental Science and Technology, 2023)

Binding of gephyrin to microtubules is regulated by its phosphorylation at Ser270 - Lin Zhou; Eva Kiss; Rebecca Demmig; Joachim Kirsch; Ralph Alexander Nawrotzki; Jochen Kuhse (Histochemistry and Cell Biology, 2021)
Gephyrin is a multifunctional scaffolding protein anchoring glycine- and subtypes of GABA type A- receptors at inhibitory postsynaptic membrane specializations by binding to the microtubule (MT) and/or the actin cytoskeleton. However, the conditions under which gephyrin can bind to MTs and its regulation are currently unknown. Here, we demonstrate that during the purification of MTs from rat brain by sedimentation of polymerized tubulin using high-speed centrifugation a fraction of gephyrin was bound to MTs, whereas gephyrin phosphorylated at the CDK5-dependent site Ser270 was detached from MTs and remained in the soluble protein fraction. Moreover, after collybistin fostered phosphorylation at Ser270 the binding of a recombinant gephyrin to MTs was strongly reduced in co-sedimentation assays. Correspondingly, upon substitution of wild-type gephyrin with recombinant gephyrin carrying alanine mutations at putative CDK5 phosphorylation sites the binding of gephyrin to MTs was increased. Furthermore, the analysis of cultured HEK293T and U2OS cells by immunofluorescence-microscopy disclosed a dispersed and punctuated endogenous gephyrin immunoreactivity co-localizing with MTs which was evidently not phosphorylated at Ser270. Thus, our study provides additional evidence for the binding of gephyrin to MTs in brain tissue and in in vitro cell systems. More importantly, our findings indicate that gephyrin-MT binding is restricted to a specific gephyrin fraction and depicts phosphorylation of gephyrin as a regulatory mechanism of this process by showing that soluble gephyrin detached from MTs can be detected specifically with the mAb7a antibody, which recognizes the Ser270 phosphorylated- version of gephyrin.

Interactions between dietary habits and home environmental exposures on respiratory symptoms in Romanian school children: an analysis of data from the SINPHONIE project - Wayne R. Lawrence; Shao Lin; Ziqiang Lin; Namratha Gurram; Iulia A. Neamtiu; Eva Csobod; Eugen Gurzau (Environmental Science and Pollution Research, 2020)

Assessment of formaldehyde levels in relation to respiratory and allergic symptoms in children from Alba County schools, Romania - Iulia A. Neamtiu; Shao Lin; Menglan Chen; Carmen Roba; Eva Csobod; Eugen S. Gurzau (Environmental Monitoring and Assessment, 2019)

Perspective: Something Old, Something New? Review of Wasting and Other Mortality in Asteroidea (Echinodermata) - Ian Hewson; Brooke Sullivan; Elliot W. Jackson; Qiang Xu; Hao Long; Chenggang Lin; Eva Marie Quijano Cardé; Justin Seymour; Nachshon Siboni; Matthew R. L. Jones; Mary A. Sewell (Frontiers in Marine Science, 2019)

Assessing associations between indoor environment and health symptoms in Romanian school children: an analysis of data from the SINPHONIE project - Jillian R. Palumbo; Shao Lin; Ziqiang Lin; Iulia A. Neamtiu; Wangjian Zhang; Eva Csobod; Eugen S. Gurzau (Environmental Science and Pollution Research, 2018)

Teacher respiratory health symptoms in relation to school and home environment - Shao Lin; Wayne R. Lawrence; Ziqiang Lin; Melissa Francois; Iulia A. Neamtiu; Qiaoxuan Lin; Eva Csobod; Eugen S. Gurzau (International Archives of Occupational and Environmental Health, 2017)

Multiplexed Fluid Flow Device to Study Cellular Response to Tunable Shear Stress Gradients - Maggie A. Ostrowski; Eva Y. Huang; Vinay N. Surya; Charlotte Poplawski; Joseph M. Barakat; Gigi L. Lin; Gerald G. Fuller; Alexander R. Dunn (Annals of Biomedical Engineering, 2016)

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)